PENGARUH PENGALAMAN VISUAL DAN AUDITORI TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI DI PAUSE CAFÉ SURABAYA - Sharon Ariella Budihartono; Victor Kurniawan Yuwono (JURNAL ILMIAH EDUNOMIKA, 2026)
This research seeks to examine the influence of auditory and visual stimuli on customer loyalty, using customer satisfaction as a mediating factor at Pause Cafe Surabaya. A quantitative approach was employed, where data were gathered via a survey method by distributing questionnaires to customers, and analyzed through Partial Least Squares (PLS) utilizing SmartPLS software. The findings indicate that both auditory and visual experiences positively and significantly impact customer satisfaction and loyalty, with visual experience exerting a stronger effect. Additionally, customer satisfaction plays a crucial role in influencing customer loyalty and can mediate the connection between auditory and visual experiences and customer loyalty, though the mediating effect is quite minimal. These results suggest that sensory experiences, especially visual and auditory components, significantly influence customer satisfaction and loyalty